2011
DOI: 10.1111/j.1532-849x.2010.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Evaluation of Four Experimental Conditioning Treatments to Improve the Bond Strength between Resin Cement and Y-TZP Ceramic

Abstract: Within the limitations of this study, additional surface treatment with air abrasion before and after sintering provided a significant increase in bond strength. Tribochemical silica coating before sintering was not effective as a surface treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
3
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 27 publications
0
34
3
18
Order By: Relevance
“…In addition, Monaco et al 20 obtained the hightest bond value with pre-sintered 110 lm Al 2 O 3 sandblasting in their study. They claimed that the values for SBS of sandblasting of pre-sintered zirconia were statistically significant, and they found that Group S compared with Group C showed higher bond values on average; however, the shear bond strengths between Group S and Group C were not significantly different (p = 0.866).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, Monaco et al 20 obtained the hightest bond value with pre-sintered 110 lm Al 2 O 3 sandblasting in their study. They claimed that the values for SBS of sandblasting of pre-sintered zirconia were statistically significant, and they found that Group S compared with Group C showed higher bond values on average; however, the shear bond strengths between Group S and Group C were not significantly different (p = 0.866).…”
Section: Discussionmentioning
confidence: 94%
“…Many surface treatments are applied for obtaining a better bond with resin cement or veneering porcelain to the surface of post-sintered ZrO 2 . 10,15,21,22,[24][25][26][27]33,34 Sandblasting, 10,15,16,[18][19][20][21][22][24][25][26][27][28][29] mechanical grinding, 16 silica coating, 20,21,25 plasma spray treatment, hydrofluoric acid treatment, 26,28 and liner 10,23 treatment are the majority of these treatments. Recently, with the development of lasers used in dentistry, a laser-etching 4,15,17,18,[24][25][26] method has been used.…”
mentioning
confidence: 99%
“…Air-borne particle abrasion, also defined as sandblasting, is usually performed by aluminum oxide particles and is one of the most commonly used mechanical methods for surface preparation of zirconia copings 3) . This technique roughens the ceramic surface and increases the surface area for bonding, thus enhancing the bond strength [27][28][29] . Some authors considered surface damage and significant removal of substances from the surface as drawbacks of the sandblasting procedure, which can cause a reduction in flexural strength of the ceramics 3,30) .…”
Section: Discussionmentioning
confidence: 99%
“…The 120 μm alumina particles provided significantly higher roughness mean values and a slightly more pronounced topography than the other three particles (Figs A, D, G, J). Monaco et al also found that for the air‐abrasion before zirconia sintering, the alumina particles (50 and 110 μm) promoted higher SBS values than the 30 μm silica‐coated ones; however, they reported no significant difference between the 50 μm and 110 μm alumina particles. It seems that, at the BS moment, the roughness may have played a more decisive role in the SBS.…”
Section: Discussionmentioning
confidence: 98%